2011
DOI: 10.1517/14728214.2011.568938
|View full text |Cite
|
Sign up to set email alerts
|

Emerging FMS-like tyrosine kinase 3 inhibitors for the treatment of acute myelogenous leukemia

Abstract: Introduction The FMS-like tyrosine kinase 3 (FLT3) is highly expressed in acute leukemias. Mutations involving FLT3 are among the most common molecular abnormalities in acute myelogenous leukemia (AML). Available evidence suggests that these molecular lesions confer a shorter disease-free survival and overall survival in patients with intermediate-risk cytogenetics. Therefore, substantial interest in FLT3 as a therapeutic target has led to the development of several promising inhibitors that target this tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…Several groups have employed various techniques to identify FLT3 resistance mutations. 1721 In contrast to the wide array of BCR-ABL resistance mutations, relatively few FLT3 resistance mutations have been identified, which may partially reflect the failure to achieve sufficient levels of inhibition of FLT3 signaling in many trials, 22 In this study, we identified the F691L and Y842C mutations previously identified as well as two novel mutations, F621L and A627P, that cause resistance to select TKI. These results suggest that novel mutations arising in FLT3/ITD, perhaps by selection during the course of treatment with a TKI, may prove to be refractory to FLT3 mutant AML management using most TKIs and emphasize the need for development of FLT3 inhibitors that can overcome resistance due to mutations.…”
Section: Introductionmentioning
confidence: 91%
“…Several groups have employed various techniques to identify FLT3 resistance mutations. 1721 In contrast to the wide array of BCR-ABL resistance mutations, relatively few FLT3 resistance mutations have been identified, which may partially reflect the failure to achieve sufficient levels of inhibition of FLT3 signaling in many trials, 22 In this study, we identified the F691L and Y842C mutations previously identified as well as two novel mutations, F621L and A627P, that cause resistance to select TKI. These results suggest that novel mutations arising in FLT3/ITD, perhaps by selection during the course of treatment with a TKI, may prove to be refractory to FLT3 mutant AML management using most TKIs and emphasize the need for development of FLT3 inhibitors that can overcome resistance due to mutations.…”
Section: Introductionmentioning
confidence: 91%
“…A number of inhibitors of FLT3 kinase activity are in clinical development, including lestaurtinib, midostaurin, sorafenib, and quizartinib [25]. Lestaurtinib was evaluated in a randomized trial where patients with first relapse of FLT3-mutataed AML were treated with chemotherapy with or without the kinase inhibitor [26].…”
Section: Molecular Targetsmentioning
confidence: 99%
“…For instance, patients with normal karyotype and NPM1 or CEBPA mutations without FLT3‐ITD mutation are no longer referred to allogeneic stem‐cell transplantation (allo‐SCT) in first complete response because their outcome is fairly good with chemotherapy alone . Additionally, therapies targeting specific molecular defects are intensively investigated, such as small molecule inhibitors of FLT3 tyrosine kinase in patients harbouring the FLT3‐ITD mutation . Among these inhibitors, sorafenib has shown some efficacy as a monotherapy in patients with relapsed FLT3‐ITD AML .…”
Section: Introductionmentioning
confidence: 99%